Rare image during laparoscopy: Abdominal tuberculosis - Karaisli, Serkan; Bağ, Halis; Peker, Yasin; Cin, Necat; Tatar, Fatma (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Karaisli S, Bağ H, Peker Y, Cin N, Tatar F. Rare Image During Laparoscopy: Abdominal Tuberculosis. Turk J Gastroenterol 2017; 28: 421-2.